Pharmacological Potential, Botany, Biological and Chemical Properties of Albuca setosa (Asparagaceae) Endemic to Southern Africa - Collen Musara; SilasM.Mudyiwa; Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2019)
Albuca setosa is a flowering bulb in the Asparagaceae family, endemic to southern Africa, thrives well on rocky ground, flats and mountain slopes. This review is an appraisal of the current information on A. setosa and a systematic and comprehensive literature search was conducted using electronic scientific journal articles, books and theses. The bulbous plant is extensively used for medicinal purposes, cultural purposes and to end quarrels between enemies. In the framework of the taxonomic revision of Albuca, a complete description of A. setosa and data on cytology, morphology, ecology and distribution and economic importance are discussed. Pharmacological screening showed that A. setosa possesses some anti-ulcerogenic, anti-inflammatory and antimicrobial properties. The bulbous plant is used for the treatment of wounds, articulation problems, rheumatoid arthritis, digestive disorder and venereal diseases.